Selectivity criterion in state aid control - Kociubiński, Jakub (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
The concept of supranational control over Member States’ measures to support undertakings operating in their territories was inserted more than fifty years ago in the original Treaty of Rome. Since then it has gained importance and now serves as a indispensable tool in maintaining Internal Market cohesion.Effective State aid control is a task of both great importance and great difficulty. The notion of State aid is nowhere to be found in the Treaties, but in its case-law the Court has established a set of cumulative criteria based largely on the wording of Article 107(1) TFEU, the fulfilment of which would lead to the designation of a State’s measure as aid. Among these, the selectivity criterion is arguably the most difficult to apply. This is for three main reasons which will be discussed in-depth in this paper.First – will a measure with limited territorial scope always be selective? Second – what differentiates ‘general’ from ‘selective’ measures, especially if the former may have incidental selective effect? Third – what does ‘nature and scheme of the system’ justification mean, and how is it applied? This paper provides an overview of practical application of the selectivity criterion in both European Commission decisions and the Court’s jurisprudence in the context of safeguarding competition and preventing subsidy races between Member States.
Keywords: supranational control; Treaty of Rome; State aid